DEVELOPMENT OF TEACHING MATERIALS BASED ON AUGMENTED REALITY (AR) IN SCIENCE SUBJECTS AT MIN 1 KOLAKA UTARA STUDENTS - Husnaini; Nurhikmah H; Awaluddin Muin; Abdul Hakim; Pattaufi (Auladuna: Jurnal Pendidikan Dasar Islam, 2023)
Abstract The low student learning outcomes in natural science at MIN 1 North Kolaka were because students had difficulty understanding abstract concepts. One of the technologies that could be utilized to visualize abstract concepts into more concrete three-dimensional objects was Augmented Reality (AR). This study aimed to measure the validity, practicality, and effectiveness of teaching-based materials in Augmented Reality in natural science learning. The research method used was Research and Development with ADDIE model. The subjects of this research were students of class V MIN 1 North Kolaka. Based on the test results obtained: (1) the result of the material and media validation test was 4.41 in the valid category, (2) the result of the practicality analysis was 80.9% in the practical category, and (3) the effectiveness result obtained from learning test was 66.7 % in the effective category and student responses were good qualifications. Therefore, teaching materials based on Augmented Reality were feasible to implement in the learning process because they were able to improve learning outcomes and attract students' attention to learning. Integrating AR into the curriculum can improve the quality of science learning in class V of elementary schools.